Analysis of the RAINBOW post-quantum electronic signature algorithm state and attacks on it for the period of the NIST PQC third round completion - Kaptiol , Ye.Yu. (Radiotekhnika, 2022)
The paper identifies and analyzes attacks aimed at cryptanalysis of the Rainbow post-quantum electronic signature algorithm and the state of this electronic signature within the framework of the NIST PQC competition and as a whole. The Rainbow electronic signature as a candidate in the third round of the NIST PQC was examined in detail for the possibility of cryptanalysis. The possibility to use this quantitative attack on the Rainbow electronic signature and the complexity of such an attack depends on the possibility to use this electronic signature in the post-quantum period. Also during the NIST PQC report on the peculiarities of the adoption of the first post-quantum standards, which took place on March 8-11, 2022, some concerns about the Rainbow’s security were mentioned due to the implementation of an attack on one of the parameter sets (although the parameter set of the second round). Some details of this attack were discussed in the paper to understand better the state of the Rainbow’s electronic signature at the end of the third round of the NIST PQC.